A new cooling method for photovoltaic panels using brine from reverse osmosis units to increase efficiency and improve productivity. (1st January 2022) - Talebnejad, Rezvan; Kamfiroozi, Shahdad; Ebadi, Hossein; Vahabi, Seyed Hossein; Sepaskhah, Ali Reza; Ghobadian, Barat; Savoldi, Laura
Highlights: A novel method for photovoltaic panel cooling was proposed using brine. Brine from reverse osmosis unit as a coolant increases electrical efficiency. Increasing feedwater temperature results in a higher permeate flow rate. The payback period will decrease by 2–4 years by using brine as a coolant. Abstract: According to the rise in the use of PV-powered reverse osmotic (RO) systems due to the current global water crisis, brine management has become a serious issue for scientists. To deal with such difficulty, this study proposes a method in which the rejected brine is used to improve the efficiency of the PV panels by cooling the PV panels and also increase the productivity of the conventional RO systems by preheating the feedwater. Thus, an experimental investigation has been performed on a stand-alone PV-powered RO system to assess the electrical and thermal performance of the solar system and to study in parallel the influence of the thermal treatment on the feeding saline water. Conducting a series of tests under five feeding temperature levels (20, 25, 30, 35, 40 °C), with three feedwater salinity levels (1500, 3000 and 4500 mg L -1 ) at the outdoor conditions, the cooling performance of the brine with various operating parameters was achieved in terms of the growth in PV electrical efficiency. The experimental results demonstrated that when the temperature of the feedwater increases, the salt rejection decreases which leads to a higher recovery factor. Moreover, for the PV cooling purpose, when the brine with temperature below or equal to the ambient temperature is used as the coolant, the temperature reduction on the PV modules is more significant. The maximum improvement in electrical efficiency was found as 3.3% on the PV panels, which shows a 20% increase compared to without cooling conditions. The economic approach also revealed that, if the conventional water used for PV cooling is replaced with the brine rejected from RO systems, the payback period will decrease by 2–4 years depending on the working parameters.